2015
DOI: 10.1080/01694243.2015.1014536
|View full text |Cite
|
Sign up to set email alerts
|

Design of multifunctional adhesives by the use of carbon nanoparticles

Abstract: We investigated the influence of carbon materials on the properties of adhesives. With the aim of the development of conductive and mechanically improved adhesives, different types of multi-walled carbon nanotubes (MWNT), single-layer graphene, graphene nanoplatelets, graphite, and carbon black were dispersed into an epoxy adhesive. For inserting particles within the viscous matrices and to obtain homogenous and stable dispersions, two different methods namely a three-roll mill and a dual asymmetric centrifuge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Inserting carbon nanotubes into adhesives has thereby improved mechanical and electrical properties of the adhesives. [2,10,11,22,27,28] The aim of this study was the enhancement of the properties of a commercially used …”
Section: Introductionmentioning
confidence: 99%
“…Inserting carbon nanotubes into adhesives has thereby improved mechanical and electrical properties of the adhesives. [2,10,11,22,27,28] The aim of this study was the enhancement of the properties of a commercially used …”
Section: Introductionmentioning
confidence: 99%
“…Tests have been carried out with functionalized carbon nanotubes used as fillers in epoxy resins that can increase the shear strength and fracture toughness of the composite together with interesting conductive properties. Since most of structural timber is glued together from lamella, the electrical modified wood-adhesive could be integrated in the production process of composite timber [46][47][48]. Recently, there has been a focus on the development of civil structures that Fig.…”
Section: Monitoring/maintenancementioning
confidence: 99%
“…There are many studies on strengthening different adhesives used in industry by means of various nanoparticle additives. Some of these studies focus on improving the thermal conductivity of the adhesives, as well as improving their resistance to external environmental conditions and their mechanical properties (Soltannia and Taheri 2014;Wehnert et al 2015;Khoramishad et al 2018;Wang et al 2021). Studies have shown that the nanoparticles additives used in different proportions have achieved considerable improvements in the thermal conductivity, resistance to environmental conditions, and adhesion strength of the adhesives.…”
Section: Introductionmentioning
confidence: 99%